The neural correlates of interference control dysfunction of working memory in major depressive disorder: An event-related potential study - Jin, Sha-yu; Zhang, Jia-zhao; Sun, Ru-hong; Jiang, Chen-guang; Wang, Jun; Zhou, Zhen-he (Frontiers in Psychiatry, 2022)
Interference control function is a key function in a series of specific functions of working memory (WM), which is usually impaired in patients with major depressive disorder (MDD). Event-related potentials (ERPs) have advantages in exploring the neural processing of interference control and WM impairment, and therefore, it is helpful to further understand the neural mechanism of MDD. In the present study, 44 patients with MDD and 44 age- and sex-matched healthy controls (HCs) were recruited. All participants completed a 4-gradient difficulty Brown-Peterson task (BPT), whose difficulty was manipulated by changing the demand of interspersed distraction tasks. High-density EEG was simultaneously recorded. The hit rate and reaction time (RT) toward the target stimulus as well as the underlying ERP features were analyzed. The results showed that, when compared with HCs, MDD patients had significantly lower hit rates and longer RTs among all four difficulties of BPT. For ERP components, no significant between-group difference was found in either N100 or P200 average amplitudes; however, the centroparietal late positive potential (LPP) amplitude of both MDD group and HC group decreased with the increase of BPT difficulty, despite the pattern of the HC group was relative moderate. For both groups, the LPP amplitude was significantly smaller in high-order difficult BPT tasks than in low-order difficult tasks. Moreover, LPP amplitude in high-order difficult tasks was much smaller in MDD group than that of HC group. Our findings suggest that failure to control interference well may play a critical role in the impairment of WM in patients with MDD, and provided new evidence that the neural correlates of interference control dysfunction of WM in MDD.